High-concentration enhanced halogen-free flame-retardant master batch for PBT (polybutylene terephthalate) as well as preparation method and application thereof
By using halogen-free flame retardant masterbatches containing copolymers and alkylphosphinates in PBT materials, the problem of insufficient flame retardant performance of existing PBT materials is solved, the application of high-concentration flame retardant and halogen-free environmental protection goals are achieved, and the flame retardant performance and mechanical properties of PBT composite materials are significantly improved.
Patent Information
- Application Number
- CN202411986994.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-31
AI Technical Summary
It is difficult for existing PBT materials to significantly improve their flame retardant properties while ensuring mechanical properties, and there are environmental protection and performance problems when using halogen-free flame retardants.
Copolymers containing non-polar saturated carbon chain segments and polar ester segments are used as carrier resins, combined with alkyl phosphinates and specific lubricants to form high concentrations of halogen-free flame retardant masterbatches and are used in PBT materials to improve flame retardant performance.
While ensuring the mechanical properties of PBT composite materials, it significantly improves its flame retardant properties, achieves halogen-free flame retardant, and has excellent mechanical properties and flame retardant properties, meeting the vertical combustion standards of V-0 grade.
Smart Images

Figure CN119735889A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-concentration enhanced halogen-free flame-retardant masterbatch for PBT and a preparation method and application thereof. Background Art
[0002] Polybutylene terephthalate, referred to as PBT, is a thermoplastic engineering plastic, which is polymerized by terephthalic acid and butanediol through a polycondensation reaction. The most widely used PBT material on the market is a product that is reinforced with glass fiber and flame-retardant modified with a halogen flame retardant (usually a bromine flame retardant), and is widely used in lighting fixtures, cooling fans, connectors, coil skeletons, electrical housings and other other electronic and electrical components. For example, patent CN101168618A (published on April 30, 2008) discloses a flame-retardant reinforced PBT resin with high strength and resistance to light aging, in which a halogen flame retardant is used to achieve flame retardancy. In recent years, with the increasing attention paid to environmental protection by the European Union and other countries in the world and the introduction of various environmental protection regulations, especially the future Rohs regulations are likely to list all halides as banned substances, so the trend of halogen-free plastic materials is irreversible, and the use of halogen-free flame retardant materials in PBT products is a development trend.
[0003] At present, the halogen-free flame retardant for modifying PBT mainly includes resorcinol bis (diphenyl phosphate) or hypophosphite, which are low-smoke and halogen-free, and can improve the flame retardant properties of polybutylene terephthalate. For example, patent CN102575106A discloses a flame retardant resin composition, which includes a thermoplastic resin and an organic phosphorus-based flame retardant, wherein the thermoplastic resin can be selected from polyethylene terephthalate, and the organic phosphorus-based flame retardant can be a phosphinate metal salt, a melamine phosphate compound, an ammonium phosphate compound, and a polyphosphazene compound. However, these halogen-free flame retardants still have some shortcomings, such as resorcinol bis (diphenyl phosphate) flame retardant is a liquid, inconvenient to use, low thermal decomposition temperature, low flame retardant efficiency, and low flame retardant anti-dripping property; hypophosphite flame retardant is easy to decompose during use, there is an explosion risk, and the mechanical properties of PBT materials will be seriously reduced.
[0004] How to significantly improve the flame retardant properties of PBT materials while ensuring their mechanical properties and making them halogen-free and environmentally friendly is a difficulty in the field of flame retardant materials. Summary of the invention
[0005] In view of the shortcomings and deficiencies of the prior art, the present invention provides an improved flame retardant for PBT. The flame retardant is used in PBT materials to significantly improve their flame retardant properties while ensuring their mechanical properties, and can achieve flame retardant and halogen-free properties.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A halogen-free flame-retardant masterbatch comprises a carrier resin and a flame retardant, wherein the carrier resin comprises a copolymer, wherein the copolymer contains a non-polar saturated carbon chain segment and a polar ester segment; the flame retardant comprises an alkyl phosphinate; and the halogen-free flame-retardant masterbatch further comprises a lubricant, wherein the lubricant is a bisamide compound formed by a saturated C12-18 acid and a diamine.
[0008] In some embodiments, the copolymer is selected from a combination of one or more of ethylene-methyl acrylate copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-ethyl methacrylate copolymer, ethylene-butyl acrylate copolymer, and ethylene-butyl methacrylate copolymer.
[0009] In some embodiments, the lubricant is ethylene bis stearamide EBS (whose structural formula is
[0010]
[0011] In some embodiments, the halogen-free flame retardant masterbatch contains 20% to 70% of carrier resin, 30% to 80% of flame retardant and 0.5% to 2.5% of lubricant in terms of mass percentage.
[0012] In some embodiments, the halogen-free flame retardant masterbatch contains 30% to 50% of carrier resin, 50% to 70% of flame retardant, and 0.5% to 2.5% of lubricant.
[0013] In some embodiments, the halogen-free flame retardant masterbatch contains 10% to 55% of alkyl phosphinate in terms of mass percentage.
[0014] In some embodiments, the halogen-free flame retardant masterbatch contains 30% to 55% of alkyl phosphinate.
[0015] In some embodiments, the alkyl phosphinate is selected from the group consisting of one or more combinations of ethyl aluminum phosphinate, butyl aluminum phosphinate, diethyl aluminum phosphinate, dibutyl aluminum phosphinate, diisobutyl aluminum phosphinate, and zinc diethyl phosphinate.
[0016] In some embodiments, the flame retardant further comprises a flame retardant synergist, and the flame retardant synergist is at least one selected from melamine polyphosphate, aluminum phosphite, and phenoxy cyclophosphazene.
[0017] In some embodiments, when the flame retardant synergist contains melamine polyphosphate, the melamine polyphosphate accounts for 10% to 30% of the mass of the halogen-free flame retardant masterbatch.
[0018] In some embodiments, when the flame retardant synergist contains aluminum phosphite, the aluminum phosphite accounts for 5% to 25% of the mass of the halogen-free flame retardant masterbatch.
[0019] In some embodiments, when the flame retardant synergist contains phenoxy cyclophosphazene, the phenoxy cyclophosphazene accounts for 1% to 5% of the mass of the halogen-free flame retardant masterbatch.
[0020] In some embodiments, the halogen-free flame retardant masterbatch further includes a charring synergist, and the charring synergist is selected from a combination of one or more of zinc borate, pentaerythritol, dipentaerythritol, sorbitol, starch, triazine charring agents, polyamide charring agents, and phenolic resin charring agents.
[0021] In some embodiments, the char-forming synergist accounts for 1% to 3% of the mass of the halogen-free flame retardant masterbatch.
[0022] In some embodiments, the halogen-free flame retardant masterbatch further includes an antioxidant.
[0023] In some embodiments, the antioxidant is selected from a combination of one or more of antioxidant 1010, antioxidant 1076, antioxidant 3114, antioxidant 3125, antioxidant 425, and antioxidant H10.
[0024] In some embodiments, the antioxidant accounts for 0.3% to 3% of the mass of the halogen-free flame retardant masterbatch.
[0025] In some embodiments, the halogen-free flame retardant masterbatch comprises the following components in terms of mass percentage:
[0026] 20% to 70% of a copolymer containing non-polar saturated carbon chain segments and polar ester segments;
[0027] Alkyl phosphinate 10% to 55%;
[0028] Phenoxy cyclophosphazene 1% to 5%;
[0029] Lubricant 0.5%~2.5%;
[0030] Carbon-forming synergist 1% to 3%;
[0031] Antioxidant 0.3%~3%.
[0032] In some embodiments, the halogen-free flame retardant masterbatch comprises the following components in terms of mass percentage:
[0033] 20% to 70% of a copolymer containing non-polar saturated carbon chain segments and polar ester segments;
[0034] Alkyl phosphinate 10% to 55%;
[0035] Melamine polyphosphate 10% to 30%;
[0036] Phenoxy cyclophosphazene 1% to 5%;
[0037] Lubricant 0.5%~2.5%;
[0038] Carbon-forming synergist 1% to 3%;
[0039] Antioxidant 0.3%~3%.
[0040] In some embodiments, the halogen-free flame retardant masterbatch comprises the following components in terms of mass percentage:
[0041] 20% to 70% of a copolymer containing non-polar saturated carbon chain segments and polar ester segments;
[0042] Alkyl phosphinate 10% to 55%;
[0043] Aluminum phosphite 5% to 25%;
[0044] Lubricant 0.5%~2.5%;
[0045] Carbon-forming synergist 1% to 3%;
[0046] Antioxidant 0.3%~3%.
[0047] In some embodiments, the halogen-free flame retardant masterbatch comprises the following components in terms of mass percentage:
[0048] 20% to 70% of a copolymer containing non-polar saturated carbon chain segments and polar ester segments;
[0049] Alkyl phosphinate 10% to 55%;
[0050] Melamine polyphosphate 10% to 30%;
[0051] Aluminum phosphite 5% to 25%;
[0052] Lubricant 0.5%~2.5%;
[0053] Carbon-forming synergist 1% to 3%;
[0054] Antioxidant 0.3%~3%.
[0055] The present invention also provides a method for preparing the above-mentioned halogen-free flame retardant masterbatch, which comprises the steps of mixing, dispersing, melt-extruding and pelletizing the raw materials.
[0056] The present invention also provides a use of the above-mentioned halogen-free flame retardant masterbatch for flame retardant polybutylene terephthalate (PBT).
[0057] The present invention also provides a halogen-free flame-retardant PBT composite material, which comprises a PBT resin and the above-mentioned halogen-free flame-retardant masterbatch.
[0058] In some embodiments, the intrinsic viscosity of the PBT resin is 0.8-1.0 dl / g. The intrinsic viscosity is measured according to ISO307 standard using Ubbelohde viscometer method.
[0059] In some embodiments, the halogen-free flame-retardant PBT composite material further includes a coupling agent and a filler.
[0060] In some embodiments, the coupling agent is selected from one or both of a silane coupling agent and a titanate coupling agent.
[0061] In some embodiments, the silane coupling agent is KH550 silane coupling agent and / or KH560 silane coupling agent.
[0062] In some embodiments, the filler is a reinforcing filler.
[0063] In some embodiments, the reinforcing filler is selected from a combination of one or more of glass fiber, basalt fiber, and carbon fiber.
[0064] In some embodiments, the reinforcing filler is a reinforcing filler treated with a coupling agent.
[0065] In some embodiments, the reinforcing filler is a reinforcing filler treated with an acrylate polymer.
[0066] In some embodiments, the acrylate polymer is a methyl methacrylate / butyl acrylate / acrylic acid copolymer.
[0067] In some embodiments, the halogen-free flame-retardant PBT composite material includes the following components, measured in parts by weight: 40-85 parts of PBT resin and 10-30 parts of halogen-free flame-retardant masterbatch.
[0068] In some embodiments, the halogen-free flame-retardant PBT composite material includes the following components, measured in parts by weight: 40-85 parts of PBT resin, 10-30 parts of halogen-free flame-retardant masterbatch, 0.1-4 parts of coupling agent, and 20-40 parts of filler.
[0069] In some embodiments, the impact strength of the halogen-free flame retardant PBT composite material is 7 to 9 KJ / m 2 , the tensile strength is 85-100MPa, the flexural strength is 128-150MPa, and the flexural modulus is 8000-9000MPa.
[0070] In some embodiments, the halogen-free flame-retardant PBT composite material has a vertical combustion rating of V-0 and an oxygen index of 33% to 35.5%.
[0071] The present invention also provides a method for preparing the aforementioned halogen-free flame-retardant PBT composite material, the preparation method comprising the steps of mixing, dispersing and melt-extruding the raw materials.
[0072] In some embodiments, the melt extrusion is performed in a twin-screw extruder.
[0073] In some embodiments, the temperature of zone 1 of the twin-screw extruder from the main feeding port to the die is 230-250°C, the temperature of zone 2 is 220-240°C, the temperature of zone 3 is 215-235°C, the temperature of zone 4 is 215-235°C, the temperature of zone 5 is 210-230°C, the temperature of zone 6 is 200-220°C, the temperature of zone 7 is 200-220°C, the temperature of zone 8 is 200-220°C, the temperature of zone 9 is 200-220°C, and the temperature of zone 10 is 210-230°C.
[0074] In some embodiments, the twin-screw extruder has an aspect ratio of 48-52:1.
[0075] In some embodiments, the screw speed of the twin-screw extruder is 350 to 550 rpm.
[0076] Compared with the prior art, the present invention has the following advantages:
[0077] The halogen-free flame retardant masterbatch of the present invention can be used for flame retardancy of PBT, and can significantly improve the flame retardancy of the PBT composite material while ensuring good compatibility with the PBT composite material and ensuring the mechanical properties of the PBT composite material, and can achieve flame retardancy and halogen-free.
[0078] The halogen-free flame retardant masterbatch of the present invention can achieve a high flame retardant concentration.
[0079] The halogen-free flame-retardant PBT composite material containing the halogen-free flame-retardant masterbatch of the present invention has excellent mechanical properties and flame-retardant properties, and its impact strength can reach 8.94KJ / m 2 , the tensile strength can reach 97.5MPa, the flexural strength can reach 145.6MPa, the flexural modulus can reach 8452MPa, while the vertical combustion grade is V-0 and the oxygen index can reach 35.5%. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] Figure 1 This is a morphology diagram of the flame retardant masterbatch in Example 1;
[0081] Figure 2 This is the morphology of the flame retardant masterbatch in Comparative Example 1;
[0082] Figure 3 This is the morphology of the flame retardant masterbatch in Comparative Example 2;
[0083] Figure 4 This is the morphology of the flame retardant masterbatch in Comparative Example 3;
[0084] Figure 5 This is the morphology of the flame retardant masterbatch in Comparative Example 4. DETAILED DESCRIPTION
[0085] The present invention provides an improved halogen-free flame retardant masterbatch. The main innovation of the product is that a copolymer containing non-polar saturated carbon chain segments and polar ester segments is used as a carrier resin. The non-polar saturated carbon chain segments in the carrier resin are flexible, which can reduce the processing difficulty of the masterbatch. The polar ester segments are similar to the PBT resin matrix structure, both of which are ester structures. The two have strong interaction and binding ability, and there will be no interface repulsion, which can improve the compatibility of the halogen-free flame retardant masterbatch and the PBT matrix resin, ensure the mechanical properties of the composite material, and at the same time, can also increase the concentration of the flame retardant in the halogen-free flame retardant masterbatch. In the halogen-free flame retardant masterbatch of the present invention, the mass percentage concentration of the flame retardant can reach up to 70%.
[0086] Another innovation of the present invention is that a specific type of lubricant is used in the halogen-free flame retardant masterbatch to improve the processing performance of the masterbatch and the compatibility with the PBT matrix resin when used. The lubricant of the present invention is a diamide compound formed by a saturated C12-18 acid and a diamine, wherein the two ends of the molecular chain are saturated non-polar long carbon chain structures and the middle is a polar diamide structure. The excellent wetting and penetration ability imparted by this symmetrical mid-polar structure improves the material processing performance and improves the melt fluidity, thereby preparing a high-concentration flame retardant masterbatch, in which the flame retardant powder concentration in the masterbatch is very high, which is difficult to achieve with ordinary existing technologies.
[0087] Another innovation of the present invention is that a flame retardant synergist is used to flame retard the alkyl phosphinate, and the flame retardant synergist is at least one selected from melamine polyphosphate, aluminum phosphite, and phenoxy cyclophosphazene. Among them, the high oxidation state phosphorus in phenoxy cyclophosphazene, alkyl phosphinate and aluminum phosphite can play a condensed phase flame retardant role during combustion, that is, when phosphorus generates phosphoric acid compounds during combustion, these phosphoric acid compounds act as dehydrating agents, and are matched with the multi-carbon structure of phenoxy cyclophosphazene to promote the dehydration and carbonization of the polymer, thereby avoiding the generation of combustible gases; and the benzene ring in phenoxy cyclophosphazene has high thermal stability, which can absorb heat during combustion, and the carbon layer structure separates air and heat from the surface of the combustion object, which can effectively prevent the continuation of combustion. In addition, the nitrogen element contained in phenoxy cyclophosphazene and melamine polyphosphate can release non-combustible gas N2 under high temperature conditions, and these gases can dilute combustible gases and oxygen, thereby inhibiting the combustion reaction. In addition, the nitrogen element can also play a flame retardant role by capturing free radicals in the combustion process and interrupting the combustion chain reaction.
[0088] The present invention is further described below in conjunction with the examples. However, the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0089] Example 1
[0090] This embodiment provides a high-concentration enhanced halogen-free flame retardant masterbatch, the mass fractions of the raw materials are shown in Table 1 below, and the preparation process is as follows:
[0091] (1) First, heat the high-speed mixer to 90° C., then weigh the raw materials except the ethylene-methyl acrylate copolymer and put them into the high-speed mixer for mixing for 20 minutes at a mixing speed of 1000 rpm.
[0092] (2) The mixture obtained in step (1) and the ethylene-methyl acrylate copolymer are respectively added to a twin-screw extruder through a precisely metered feeder, and the mixture is mixed, dispersed, melt-extruded, and pelletized to obtain a flame retardant masterbatch.
[0093] In step (2), the temperature of zone 1 of the twin-screw extruder from the main feed port to the die is 180°C, the temperature of zone 2 is 180°C, the temperature of zone 3 is 175°C, the temperature of zone 4 is 175°C, the temperature of zone 5 is 160°C, the temperature of zone 6 is 160°C, the temperature of zone 7 is 160°C, the temperature of zone 8 is 150°C, the temperature of zone 9 is 150°C, the temperature of zone 10 is 170°C, and the screw speed is 350 rpm.
[0094] The flame retardant masterbatch is used to prepare halogen-free flame retardant PBT composite materials:
[0095] (1) According to the mass percentage, 44.5% PBT resin (with an intrinsic viscosity of 0.9 dl / g), 25% of the flame retardant masterbatch, 0.5% of KH550 coupling agent, and 30% of glass fiber (glass fiber treated with methyl methacrylate / butyl acrylate / acrylic acid copolymer) were put into a high-speed mixer and mixed for 10 minutes at a mixing speed of 900 rpm.
[0096] (2) The mixture obtained in step (1) is fed into a twin-screw extruder through a main feed port for mixing, dispersion, melt extrusion, and pelletizing.
[0097] In step (2), the temperature of the first zone of the twin-screw extruder from the main feed port to the die is 240°C, the temperature of the second zone is 235°C, the temperature of the third zone is 235°C, the temperature of the fourth zone is 230°C, the temperature of the fifth zone is 230°C, the temperature of the sixth zone is 220°C, the temperature of the seventh zone is 220°C, the temperature of the eighth zone is 210°C, the temperature of the ninth zone is 210°C, the temperature of the tenth zone is 230°C, and the screw speed is 450 rpm. The test specimen is injection molded by an injection molding machine at 255°C.
[0098] Embodiment 2-9
[0099] This embodiment provides a high-concentration enhanced halogen-free flame-retardant masterbatch, and uses it to prepare a halogen-free flame-retardant PBT composite material, which is basically the same as Example 1, except that the raw material composition and dosage are different, see Table 1 for details.
[0100] Example 10
[0101] The method is basically the same as Example 2, except that when preparing the halogen-free flame-retardant PBT composite material, the raw material composition is adjusted to: 51.5% PBT resin, 18% flame-retardant masterbatch, 0.5% KH560 coupling agent, and 30% glass fiber treated with methyl methacrylate / butyl acrylate / acrylic acid copolymer according to mass percentage.
[0102] Comparative Example 1
[0103] This comparative example provides a high-concentration enhanced halogen-free flame retardant masterbatch, and uses it to prepare a halogen-free flame retardant PBT composite material, which is basically the same as Example 2, except that the raw material ethylene-methyl acrylate copolymer of the flame retardant masterbatch is replaced with PBT resin.
[0104] Comparative Example 2
[0105] This comparative example provides a high-concentration enhanced halogen-free flame retardant masterbatch, and uses it to prepare a halogen-free flame retardant PBT composite material, which is basically the same as Example 2, except that the raw material ethylene-methyl acrylate copolymer of the flame retardant masterbatch is replaced by polyethylene resin.
[0106] Comparative Example 3
[0107] This comparative example provides a high-concentration enhanced halogen-free flame retardant masterbatch, and uses it to prepare a halogen-free flame retardant PBT composite material, which is basically the same as Example 2, except that the raw material of the flame retardant masterbatch, ethylene bisstearamide EBS, is replaced by ethylene bisoleamide EBO.
[0108] Comparative Example 4
[0109] This comparative example provides a high-concentration enhanced halogen-free flame retardant masterbatch, and uses it to prepare a halogen-free flame retardant PBT composite material, which is basically the same as Example 2, except that the raw material of the flame retardant masterbatch, ethylene bisstearamide EBS, is replaced by octadecyl alcohol (stearyl alcohol).
[0110] Comparative Example 5
[0111] The comparative example provides a halogen-free composite powder flame retardant, and the same is used to prepare a halogen-free flame-retardant PBT composite material. The raw materials of the flame retardant are, by weight, 572 parts of diethyl aluminum phosphinate, 143 parts of melamine polyphosphate, 207 parts of aluminum phosphite, 36 parts of phenoxy cyclophosphazene, 14 parts of ethylene bis stearamide EBS, 21 parts of anhydrous zinc borate and 7 parts of antioxidant H10. The preparation method of the flame retardant is: firstly heating a high-speed mixer to 90°C, then weighing the raw materials and putting them into the high-speed mixer for mixing, the mixing time is 20min, and the mixing speed is 1000 rpm, to prepare the halogen-free composite powder flame retardant.
[0112] Preparation of halogen-free flame-retardant PBT composite material: basically the same as Example 2, except that the flame-retardant masterbatch in Example 2 is replaced by the halogen-free compound powder flame retardant of this comparative example.
[0113] Table 1
[0114]
[0115] In Table 1, the ethylene-methyl acrylate copolymer is: 29MA03T. “ / ” represents none.
[0116] The mechanical properties and flame retardant properties of the PBT composite materials of each embodiment and comparative example were tested by impact strength (GB / T1843-2008), flexural strength (GB / T9341-2008), tensile strength (GB / T1040.2-2006), oxygen index (GB / T2406.2-2009), vertical combustion (GB / T2408-2008) and other methods, and the results are shown in Table 2.
[0117] Table 2
[0118]
[0119] The morphology of the flame retardant masterbatch of Example 1 and Comparative Examples 1-4 are as follows: Figure 1-5 As shown, it can be seen that the flame retardant masterbatch of Example 1 using the scheme of the present invention is in granular form and has good moldability, while the flame retardant masterbatch of Comparative Examples 1-4 which do not use the masterbatch carrier resin and the specific type of lubricant of the present invention either cannot be obtained in granular form and is still in powder form, or there are black fine lines on the side of the prepared particles, which affects the appearance and performance ( Figure 4 Otherwise, during the processing, the surface of the particles will turn yellow due to oxidation, affecting the appearance and performance of the particles ( Figure 5 ).
[0120] From the comparison between Example 1 and Comparative Examples 1-2, it can be seen that when the specific type of carrier resin of the present invention is not used, the flame retardant masterbatch obtained is used for PBT material, and the flame retardant efficiency is low and the mechanical properties are poor due to poor compatibility. From the comparison between Example 1 and Comparative Examples 3-4, it can be seen that when the specific type of lubricant of the present invention is not used, the flame retardant masterbatch obtained is used for PBT material, and the mechanical properties are poor due to poor dispersibility. From the comparison between Example 2 and Comparative Example 5, it can be seen that the flame retardant masterbatch is easier to process and disperse into the material than the traditional powder flame retardant, and the flame retardant performance and mechanical properties are improved.
[0121] It can be seen that when the halogen-free flame retardant masterbatch of the present invention is used for PBT material, the mechanical properties of the PBT composite material can be guaranteed, while significantly improving its flame retardant properties, such as vertical burning grade and oxygen index, etc., and the flame retardant masterbatch of the present invention is halogen-free and more environmentally friendly.
[0122] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
[0123] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
Claims
1. A halogen-free flame retardant masterbatch, comprising a carrier resin and a flame retardant, characterized in that: The carrier resin includes a copolymer containing a non-polar saturated carbon chain segment and a polar ester segment; the flame retardant includes an alkyl phosphinate; the halogen-free flame retardant masterbatch also includes a lubricant, which is a bisamide compound formed by a saturated C12-18 acid and a diamine.
2. The halogen-free flame retardant masterbatch according to claim 1, characterized in that: The copolymer is selected from the group consisting of one or more combinations of ethylene-methyl acrylate copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-ethyl methacrylate copolymer, ethylene-butyl acrylate copolymer, and ethylene-butyl methacrylate copolymer.
3. The halogen-free flame retardant masterbatch according to claim 1, characterized in that: The lubricant is ethylene bisstearamide.
4. The halogen-free flame retardant masterbatch according to claim 1, characterized in that: In terms of mass percentage, the halogen-free flame retardant masterbatch contains 20% to 70% of carrier resin, 30% to 80% of flame retardant and 0.5% to 2.5% of lubricant; preferably, the halogen-free flame retardant masterbatch contains 30% to 50% of carrier resin, 50% to 70% of flame retardant and 0.5% to 2.5% of lubricant.
5. The halogen-free flame retardant masterbatch according to claim 1, characterized in that: In terms of mass percentage, the halogen-free flame retardant masterbatch contains 10% to 55% of alkyl phosphinate; preferably, the halogen-free flame retardant masterbatch contains 30% to 55% of alkyl phosphinate.
6. The halogen-free flame retardant masterbatch according to claim 1, characterized in that: The alkyl phosphinate is selected from the group consisting of one or more of ethyl phosphinate aluminum, butyl phosphinate aluminum, diethyl phosphinate aluminum, dibutyl phosphinate aluminum, diisobutyl phosphinate aluminum, and diethyl zinc phosphinate.
7. The halogen-free flame retardant masterbatch according to claim 1, characterized in that: The flame retardant further comprises a flame retardant synergist, and the flame retardant synergist is at least one selected from melamine polyphosphate, aluminum phosphite, and phenoxy cyclophosphazene.
8. The halogen-free flame retardant masterbatch according to claim 7, characterized in that: When the flame retardant synergist contains melamine polyphosphate, the melamine polyphosphate accounts for 10% to 30% of the mass of the halogen-free flame retardant masterbatch; and / or, when the flame retardant synergist contains aluminum phosphite, the aluminum phosphite accounts for 5% to 25% of the mass of the halogen-free flame retardant masterbatch; and / or, when the flame retardant synergist contains phenoxy cyclophosphazene, the phenoxy cyclophosphazene accounts for 1% to 5% of the mass of the halogen-free flame retardant masterbatch.
9. The halogen-free flame retardant masterbatch according to claim 1, characterized in that: The halogen-free flame retardant masterbatch further comprises a carbon-forming synergist, and the carbon-forming synergist is selected from a combination of one or more of zinc borate, pentaerythritol, dipentaerythritol, sorbitol, starch, triazine carbon-forming agent, polyamide carbon-forming agent, and phenolic resin carbon-forming agent.
10. The halogen-free flame retardant masterbatch according to claim 9, characterized in that: The carbon-forming synergist accounts for 1% to 3% of the mass of the halogen-free flame-retardant masterbatch.
11. The halogen-free flame retardant masterbatch according to claim 1, characterized in that: The halogen-free flame retardant masterbatch also includes an antioxidant.
12. The halogen-free flame retardant masterbatch according to claim 11, characterized in that: The antioxidant is selected from one or more combinations of antioxidant 1010, antioxidant 1076, antioxidant 3114, antioxidant 3125, antioxidant 425, and antioxidant H10; and / or, the antioxidant accounts for 0.3% to 3% of the mass of the halogen-free flame retardant masterbatch.
13. The halogen-free flame retardant masterbatch according to claim 1, characterized in that: In terms of mass percentage, the halogen-free flame retardant masterbatch comprises the following components: 20% to 70% of a copolymer containing non-polar saturated carbon chain segments and polar ester segments; Alkyl phosphinate 10% to 55%; Phenoxy cyclophosphazene 1% to 5%; Lubricant 0.5%~2.5%; Carbon-forming synergist 1% to 3%; Antioxidant 0.3%~3%.
14. The halogen-free flame retardant masterbatch according to claim 1, characterized in that: In terms of mass percentage, the halogen-free flame retardant masterbatch comprises the following components: 20% to 70% of a copolymer containing non-polar saturated carbon chain segments and polar ester segments; Alkyl phosphinate 10% to 55%; Melamine polyphosphate 10% to 30%; Phenoxy cyclophosphazene 1% to 5%; Lubricant 0.5%~2.5%; Carbon-forming synergist 1% to 3%; Antioxidant 0.3%~3%.
15. The halogen-free flame retardant masterbatch according to claim 1, characterized in that: In terms of mass percentage, the halogen-free flame retardant masterbatch comprises the following components: 20% to 70% of a copolymer containing non-polar saturated carbon chain segments and polar ester segments; Alkyl phosphinate 10% to 55%; Aluminum phosphite 5% to 25%; Lubricant 0.5%~2.5%; Carbon-forming synergist 1% to 3%; Antioxidant 0.3%~3%.
16. The halogen-free flame retardant masterbatch according to claim 1, characterized in that: In terms of mass percentage, the halogen-free flame retardant masterbatch comprises the following components: 20% to 70% of a copolymer containing non-polar saturated carbon chain segments and polar ester segments; Alkyl phosphinate 10% to 55%; Melamine polyphosphate 10% to 30%; Aluminum phosphite 5% to 25%; Lubricant 0.5%~2.5%; Carbon-forming synergist 1% to 3%; Antioxidant 0.3%~3%.
17. A method for preparing the halogen-free flame retardant masterbatch according to any one of claims 1 to 16, characterized in that: The preparation method comprises the steps of mixing, dispersing, melt-extruding and pelletizing various raw materials.
18. Use of the halogen-free flame retardant masterbatch according to any one of claims 1 to 16 for flame retardant polybutylene terephthalate (PBT).
Citation Information
Patent Citations
Light aging resisting and high-strength anti-flaming enhancement polybutylene terephthalate composition and preparation method thereof
CN101168618A
Flame-retardant resin composition, and insulated electric wire, flat cable, and molded article, which are made using same
CN102575106A
PBT (Polybutylece Terephthalate) special halogen and phosphorus free inflaming retarding plasticizing mother particle and preparation method thereof
CN101798447A
Toughening and reinforcing flame-retardant master batch
CN103709648A
Special halogen-free flame-retardant synergistic functional master batch for PBT resin modification, and preparation method thereof
CN110577698A